2018
DOI: 10.1016/j.wneu.2018.03.091
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Spine Tumor Epidemiology: Comparison of Trends in Surgery Across Two Decades and Three Continents

Abstract: Surgical habits have been fairly consistent among countries worldwide and over time. However, patient survival has improved in later years, perhaps due to medical advances in the treatment of cancer, improved patient selection, and operating earlier in the course of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 24 publications
3
49
1
2
Order By: Relevance
“…Perhaps these results are regional characteristics peculiar to the three-neurosurgical divisions operating profiles inserted into their Heath Institutions contexts. This knowledge is in accordance to Wright et al, 2018 (28) that surgical habits have been fairly consistent among countries worldwide and over time, as reported in a comparative study of trends in surgery across two decades and three continents in metastatic spine tumor epidemiology.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps these results are regional characteristics peculiar to the three-neurosurgical divisions operating profiles inserted into their Heath Institutions contexts. This knowledge is in accordance to Wright et al, 2018 (28) that surgical habits have been fairly consistent among countries worldwide and over time, as reported in a comparative study of trends in surgery across two decades and three continents in metastatic spine tumor epidemiology.…”
Section: Discussionsupporting
confidence: 92%
“…analyzed patients with spinal metastases from the Netherlands and found that the most common primary tumor was breast cancer, followed by lung cancer, prostate cancer, kidney cancer, and others. Similarly, an epidemiological study of spinal metastases across two decades and three continents showed that the most common primary tumor was breast cancer, followed by prostate cancer, lung cancer, kidney cancer, and others. A nationwide epidemiological study of adult Koreans with spinal metastases showed that the most common primary tumor was lung cancer, followed by liver cancer, breast cancer, colon cancer, and others.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of epidemiological studies on spinal metastases has been gradually increasing worldwide. A spinal metastases epidemiology study that compared surgery trends across two decades and three continents concluded that surgical habits had been fairly consistent among countries worldwide and over time. Moreover, the study of Sohn et al .…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological survey based on a population of spinal metastases in South-East Norway showed that prostate cancer, lung cancer and breast cancer accounted for 66% of all patients, followed by myeloma, lower gastrointestinal tumor, kidney cancer and tumors of unknown origin [7]. Another study comparing trends in surgical treatments of spinal metastases across two decades and three continents noted that colon cancer, liver cancer and lung cancer accounted for a higher proportion in Asian countries, while breast cancer, prostate cancer and myeloma had a lower proportion [18]. The authors believed that the difference was largely dependent on the different high-prevalence cancer types and different early screening programs in different parts of the world.…”
Section: Primary Tumor Typementioning
confidence: 99%
“…However, in more developed countries, prostate cancer is the most common cancer among male patients and lung cancer is the leading cause of cancer death among female patients [19]. In addition, the incidence of liver cancer in China is more than three times than that in North America and 10 times than that of some European countries; while the incidence of breast cancer in China is lower than that in North America [18].…”
Section: Primary Tumor Typementioning
confidence: 99%